Analisis Framing Berita Bencana Banjir di Sumatera Utara Tahun 2025 pada Media Kompas.com - Siti Aisya Purba; Erwan Efendi (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2026)
This study investigates how Kompas.com, a leading Indonesian online news platform, framed the devastating flood disaster that struck North Sumatra between late November and early December 2025. Guided by Robert N. Entman's (1993) framing model, comprising problem definition, causal diagnosis, moral evaluation, and treatment recommendation, the research applies qualitative framing analysis to eight Kompas.com news articles published between 25 November and 1 December 2025. Findings show that coverage evolved thematically: early reports emphasized humanitarian emergency and casualties, subsequent articles shifted toward environmental governance and political accountability, and later coverage affirmed the state's institutional response through presidential visits and police-led logistical aid. Ecological drivers such as deforestation and illegal logging, however, received markedly limited elaboration. This pattern indicates that Kompas.com privileged disaster impact and institutional response over structural ecological causation, shaping public understanding of the 2025 North Sumatra flood as a layered yet incompletely explained crisis.